Financial liquidity analysis of CSR based Capital Group Zywiec SA - Aleksandra Gasior (Amfiteatru Economic Journal, 2013)
The article presents the Capital Group Grupa Zywiec plc. as an enterprise operating in food industry which has received a Golden Leaf Award for CSR” (Pichola, Rudzki, 2013) and has been ranked among the top ten companies in the aforementioned sector. It is a beer producer, i.e. a good which is controversial in the opinion of society. In order to change the attitude of the public toward the Capital Group and show concern for ecological aspects, the company has made attempts to create and implement CSR strategy in formal terms. It should be emphasized that major shareholder (Heineken company) has already been following the strategy of sustainable development referred to as Brewing a Better Future (Social Report, 2013). However, the period during which the aforementioned actions were taken arouses a number of doubts, e.g. if the enterprise is able to continue its activity having achieved a certain level of liquidity. In times of great financial crisis, which started at the turn of 2007 and 2008, maintaining adequate liquidity was the main problem. It was then that enterprises ought to pay special attention to this aspect (Gorczynska, 2011; Raport, 2010). Having the above in mind, the paper discusses issues relating to financial liquidity of the Capital Group Zywiec plc. in times of economic crisis and at the initial stage of CSR strategy implementation. Case study is the main method employed to verify the hypothesis formulated at the beginning of the article. Selected financial ratios are used in order to compare the liquidity of the Capital Group with the liquidity of the entire sector.
Keywords: G17; G34; Q56; 330; Sustainable development; capital group; financial analysis; liquidity